Pelaksanaan Pendidikan Pemakai di Perpustakaan Universitas Negeri Padang - Trinanda, Lisa; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
This article aims to determine: (1) how the implementation of user education in Padang State University Library; (2) the obstacles encountered in the implementation of user education in Padang State University Library; and (3) efforts in the face of constraints on the implementation of user education Padang State University Library. Data were collected through direct observation and interviews with librarians at the Library of the State University of Padang. Analyzing data descriptively.By analyzing the data, we can conclude the following: First, the implementation of user education in Padang State University Library uses a lecture and tour of the library. The medium used is a power point and printed materials. Understanding the material provided in the form of a library, the purpose of the library, library functions, types of collections, the room layout, how to browse through collections and library rules. Second, the obstacles encountered in the implementation of user education in Padang State University Library is not used a megaphone and a lack of instructors implementers when implementing user education. Third, the efforts made to overcome these obstacles is the library must provide a megaphone and add instructors implementers when implementing user education. Keywords: implementation, education, user.